ANALISIS KESESUAIAN SAK ETAP DENGAN PP NO 46 TAHUN 2013 BAGI PELAKU UMKM - Widya Pratiwi; Muhammad Nasir (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
SAK ETAP was one finance accountancy standard that was tended for UMKM. The SAK ETAP was arranged by IAI under shade of finance ministry. Where PP number 46 year 2013 was one tax regulation for UMKM with other words for entity that had gross currency under 4,8 miliard. Althrough both of the regulation were fended for UMKM, however many diverifications that were found and one of them about application of tax regulation that was not prnted in SAK ETAP. This research purposed to see the content and purpose of SAK ETAP and PP number 46 year 2013 as well as suitability about both of the regulations. The method that was used in this research was normative zuridical. The approach that was used in this research was conceptual approach. The technique to collect the data was primary that was SAK ETAP and PP number 46 year 2013 as well as Pph article 4 paragraph 2 and secondary constitute research results that related with accountancy and tax. The discussion of this research found that SAK ETAP contained about the way to regulate the registration of accountancy more simply than general SAK in confession case and disclosure of transaction in finance report. SAK ETAP had purpose in order that UMKM in Indonesia could arranged the finance report based on SAK that was valid with simply registration to find financing access from outside where as the content of PP number 46 year 2013 countined about ultimate tax that had final duality and tariff fare tax to ultimate from exertion that was acceptanced by tax obliglatory thad gross currency less than 4,8 milliard and as a purpose to give ease in tax determination that was fixed 0,5% from the gross currency. The suitability of content and purpose between SAK ETAP and PP number 46 year 2013 located in purpose that were tended to UMKM and geve some eases for UMKM. SAK ETAP gave ease for UMKM to arrange the finance report that simple while PP number 46 year 2013 gave ease for tax determination. Meanwhile, from content side found basic diversity beturden both of the regulations, that was SAK ETAP did not give instruction of UMKM in gross currency explanation that directly related with taxation determination